2002
DOI: 10.1118/1.1510130
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental quantification of carotid plaque volume measurements made by three‐dimensional ultrasound using test phantoms

Abstract: An accurate technique that exhibits low variability has practical importance for the quantification of carotid plaque volume. Such a technique is necessary to monitor plaque progression or regression that may result in response to nonsurgical therapy. In this study, we investigate the accuracy and variability of plaque volume measurement by three-dimensional ultrasound using vascular plaque phantoms over a range of 68.2 mm3 to 285.5 mm3. The agar plaques maintained a consistent cylindrical geometry with variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 19 publications
2
48
0
1
Order By: Relevance
“…Our values of 6.5% and 6.9% obtained for the intraobserver and interobserver measurement variability of the plaques investigated are comparable to the corresponding variability reported by Delcker et al, 14 -16 as well as the results obtained in vitro on plaque phantoms. 19 In addition, coefficients of reliability in our study were similar to those reported by other investigators and very close to unity (see Table 2) for intraobserver and interobserver measurements, suggesting clinical utility. 17 Although other investigators have measured plaque volume spanning a similar range as ours, 17,18 our study differs in that we have reported the intraobserver and interobserver variabilities as a function of plaque volume.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our values of 6.5% and 6.9% obtained for the intraobserver and interobserver measurement variability of the plaques investigated are comparable to the corresponding variability reported by Delcker et al, 14 -16 as well as the results obtained in vitro on plaque phantoms. 19 In addition, coefficients of reliability in our study were similar to those reported by other investigators and very close to unity (see Table 2) for intraobserver and interobserver measurements, suggesting clinical utility. 17 Although other investigators have measured plaque volume spanning a similar range as ours, 17,18 our study differs in that we have reported the intraobserver and interobserver variabilities as a function of plaque volume.…”
Section: Discussionsupporting
confidence: 90%
“…19 The initial slice location and the variability in the plaque boundary for each slice are not dependent on selection of the ISD. Therefore, the nonlinear relation between measurement accuracy and ISD (Figure 4) is a result of the inaccurate determination of the final edge of the plaque for ISDs Ͼ3.0 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously described, 17,18 TPV was measured with a software update permitting semiautomated segmentation of the lumen.…”
mentioning
confidence: 99%
“…Gain, focal points and time-depth compensation were optimized by the sonographer taking into consideration neck size, carotid anatomy and tissue depth. Two dimensional images were reconstructed into a 3D volume as previously described (39,40). MRI was performed on a whole body 3.0 Tesla Discovery 750MR (General Electric Health Care, Milwaukee, Wisconsin, USA) MRI system.…”
Section: Image Acquisitionmentioning
confidence: 99%